2008
DOI: 10.1111/j.1524-4741.2007.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Node Procedure is Warranted in Ductal Carcinoma In Situ with High Risk of Occult Invasive Carcinoma and Microinvasive Carcinoma Treated by Mastectomy

Abstract: Axillary lymph node dissection in patients with ductal carcinoma in situ (DCIS) of the breast is not warranted because DCIS has no metastatic potential. However, the risk of microinvasive carcinoma (MIC) exists in large DCIS treated by mastectomy. The aim of this series is to evaluate the incidence of lymph node metastases in DCIS and DCIS-MIC. We analyzed retrospectively patients treated in six French cancer centers for pure DCIS or DCIS-MIC. Surgical procedures were lumpectomy or mastectomy associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 32 publications
1
14
0
2
Order By: Relevance
“…In theory, there is no axillary lymph node involvement in DCIS, although a recent review has reported 1.4% involvement in 1621 patients with pure DCIS (Morrow et al, 2002;Leonard and Swain, 2004). There may, however, be a risk of associated microinvasive foci, especially when the lesion is extensive (McMasters et al, 2002;Moran et al, 2005;Tunon de Lara et al, 2008). This may be a reason why, even though axilla management is pointless, 10.4% of our patients underwent AD and 21.3% underwent SNB.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In theory, there is no axillary lymph node involvement in DCIS, although a recent review has reported 1.4% involvement in 1621 patients with pure DCIS (Morrow et al, 2002;Leonard and Swain, 2004). There may, however, be a risk of associated microinvasive foci, especially when the lesion is extensive (McMasters et al, 2002;Moran et al, 2005;Tunon de Lara et al, 2008). This may be a reason why, even though axilla management is pointless, 10.4% of our patients underwent AD and 21.3% underwent SNB.…”
Section: Discussionmentioning
confidence: 79%
“…In our study, SNB rate was 12.3% after CS vs 41.7% after mastectomy (Po0.001). Finally, a recent French multicentric study (Tunon de Lara et al, 2008) including 116 large DCIS found 4 positive sentinel nodes (3.4%). Thus, SNB could be proposed in patients treated by mastectomy.…”
Section: Discussionmentioning
confidence: 92%
“…Although SLNB is a less invasive procedure compared with axillary lymph node dissection (ALND), it is associated with a certain degree of morbidity and may lead to overdiagnosis and overtreatment [6] . Paresthesias, lymphedemas, and seromas have also been reported [7,8] . Therefore, the role of SLNB in DCIS is controversial and the indications for its use are not clear.…”
Section: Introductionmentioning
confidence: 95%
“…Second, a SLNB will be unnecessary in the majority of patients with a preoperative image-guided CNB diagnosis of DCIS because the final postoperative histology will only contain pure DCIS and will not contain any invasive disease [2,19] . Third, although SLNB is a less morbid surgical procedure compared with ALND, it is also associated with complications [7,8] . Fourth, SLNB can also lead to excessive and unnecessary treatment by providing misleading information about the axillary status.…”
Section: Al-ameer Ay Et Al Snlb In Clinically Detected Dcismentioning
confidence: 99%
“…In the few cases published in the literature [63,[68][69][70][78][79][80][81], in which AD was performed after an positive SLNB, in all cases but one (67/68, 98,5%) all the non-SLNs were negative and the SLN already biopsied was the only positive LN. That is why we conclude that in cases of DIN patients with a positive SLNB, AD should not be immediately performed except for only those cases that present mammary invasion on final pathologic evaluation.…”
Section: Surgical Treatmentmentioning
confidence: 99%